2002
DOI: 10.1093/emboj/cdf289
|View full text |Cite
|
Sign up to set email alerts
|

INK4a-deficient human diploid fibroblasts are resistant to RAS-induced senescence

Abstract: The CDKN2A tumour suppressor locus encodes two distinct proteins, p16 INK4a and p14 ARF , both of which have been implicated in replicative senescence, the state of permanent growth arrest provoked in somatic cells by aberrant proliferative signals or by cumulative population doublings in culture. Here we describe primary ®broblasts from a member of a melanomaprone family who is homozygous for an intragenic deletion in CDKN2A. Analyses of the resultant gene products imply that the cells are p16 INK4a de®cient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
191
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(204 citation statements)
references
References 51 publications
11
191
0
1
Order By: Relevance
“…Next, we took advantage of the Leiden strain of human fibroblasts that carry a mutation that functionally inactivates both copies of p16 INK4a (Brookes et al ., 2002). Immunostaining revealed that the levels of the altered protein in Leiden fibroblasts are lower than those of wild‐type p16 INK4a in IMR90 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we took advantage of the Leiden strain of human fibroblasts that carry a mutation that functionally inactivates both copies of p16 INK4a (Brookes et al ., 2002). Immunostaining revealed that the levels of the altered protein in Leiden fibroblasts are lower than those of wild‐type p16 INK4a in IMR90 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Leiden human fibroblasts have been previously described (Brookes et al ., 2002). Cells were maintained in Dulbecco's modified Eagle's medium (Invitrogen, Paisley, UK) with 10% foetal bovine serum (PAA, Amersham, UK) and 1% antibiotic–antimycotic solution (Invitrogen, Paisley, UK).…”
Section: Methodsmentioning
confidence: 99%
“…In mouse cells, activated oncogenes also activate p53 by upregulation of p14ARF. However, this pathway is apparently not conserved in human cells (17,42,132). Activation of the p53 pathway contributes to activation of the pRB pathway.…”
Section: Senescence Inducing Pathwaysmentioning
confidence: 99%
“…A complementary approach to understanding the role of p16 INK4A in suppressing transformation is the use of p16 INK4A -deficient fibroblasts (Leiden cells) (Brookes et al 2002;Drayton et al 2003). These human cells have a homozygous deletion in INK4A that renders them 16 INK4A deficient, yet they translate a protein that retains some of the known functions of p14 ARF (Brookes et al 2002).…”
Section: Sv40 Lt Antigen: Inhibiting the Rb/p16 Ink4a And P53/p14 Arfmentioning
confidence: 99%
“…These human cells have a homozygous deletion in INK4A that renders them 16 INK4A deficient, yet they translate a protein that retains some of the known functions of p14 ARF (Brookes et al 2002). Co-expression of hTERT, c-Myc, and RAS in Leiden cells, but not in control p16 INK4A -expressing fibroblasts, allows for tumor formation in immunocompromised mice, but at long latency and low frequency (Drayton et al 2003).…”
Section: Sv40 Lt Antigen: Inhibiting the Rb/p16 Ink4a And P53/p14 Arfmentioning
confidence: 99%